2021 9th International Conference on Information and Communication Technology (ICoICT) 2021
DOI: 10.1109/icoict52021.2021.9527477
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Online Recruitment Fraud Using Machine Learning

Abstract: Online Recruitment fraud (ORF) is becoming an important issue in the cyber-crime region. Companies find it easier to hire people with the help of the internet rather than the old traditional way. But it has greatly attracted the scammers to deceive people and exploit their information. There have been lots of incidents where innocent people have fallen for this malicious fraud and lost millions of money. Even it causes harm to business and the economy. Unlike other cyber-security problems, like email spam, phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Our experimental findings reveal an accuracy of 91.86%, a precision value of 0.898, and a recall value of 0.695, which exceeds the reported measures in terms of accuracy and precision. The work by Tabassum, et al [29], reported accuracies within the approximate range of 94-96%. However, the research did not report any other performance measure, such as, precision or recall, to demonstrate the robustness of their proposed approach.…”
Section: Experimental Findings and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our experimental findings reveal an accuracy of 91.86%, a precision value of 0.898, and a recall value of 0.695, which exceeds the reported measures in terms of accuracy and precision. The work by Tabassum, et al [29], reported accuracies within the approximate range of 94-96%. However, the research did not report any other performance measure, such as, precision or recall, to demonstrate the robustness of their proposed approach.…”
Section: Experimental Findings and Discussionmentioning
confidence: 95%
“…As outlined in the related work section, apart from our proposed work, only two other research works [28], [29] considered focusing on localised factors. However, they were conducted under Indonesian and Bangladeshi contexts, respectively.…”
Section: Experimental Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AB is an ensemble ML method that aims to integrate several weak classifiers and transform them into strong ones [ 38 ]. In this method, DT is used as a default base estimator for training the model.…”
Section: Methodsmentioning
confidence: 99%
“…The study of Anita et al (2021) used logistic regression (LR), k-nearest neighbor (k-NN), Random Forest (RF), and deep learning (DL) algorithms for detecting fraudulent jobs from a large pool of real data and found that DL performed best. Another study by Tabassum et al (2021) applied seven different ML algorithms and found the highest accuracy of two classifiers at 95.17%. The study of Alghamdi & Alharby (2019) created a prediction model using an RF algorithm for preventing fraudulent jobs and achieved 97.41% accuracy.…”
Section: Related Workmentioning
confidence: 99%